Pengembangan Kapasitas Masyarakat Partisipatif: Studi Implementasi Program Saemaul Undong Di Kabupaten Gunung Kidul DIY - Dewi Cahyani Puspitasari; Rina Satriani; Sri Bintang Pmungkas (Faculty of Social Science, Universitas Negeri Malang, 2019)
Saemaul Undong program implementation in DI Yogyakarta province is the result of sister province cooperation between government of DI Yogyakarta which represented by the Agency of Women and Community Empowerment and Gyeongsangbuk-do province, South Korea which represented by Saemaul Global Foundation (SGF). The focus of program are farming and women empowerment where Bleberan village, Gunung Kidul regency as one of implementation area. The aim of research are, first, to learn the condition, potency, and the challenge of Saemaul Undong program implementation; second, to learn the participation process and the strategy chance of community empowerment. The method of research is qualitative evaluation by elaborating survey, literature review, interview, and focus group discussion. Qualitative analyse is done making deep description and survey analyse is matching the characteristic of result. The result showed that Saemaul Undong program implementation Bleberan village has good response and can bridging the relation between government and community in village farming development. Besides that, Saemaul Undong program also improved the spirit of self-quality development through sharing experience and knowledge. The consequents are persuasion process to make others people interest to this program quite hard. The strategy of capacity building of organization, access improvement, and infrastructure development, strengthening system capacity, improvement of skill and income is a form of collaboration and result of cooperation inter sector between village government and Saemaul Undong Global Foundation.